High temperature susceptibility measurements: A potential tool for the identification of oil-water transition zone in petroleum reservoirs - Abdulkarim, Maryam A.; Muxworthy, Adrian R.; Fraser, Alastair (Frontiers in Earth Science, 2022)
Determining the position and thickness of the oil water transition zone (OWTZ) in hydrocarbon reservoirs is important to reserve estimation and production planning. This paper describes a magnetic method of identifying this zone. High temperature susceptibility (HT-χ) measurements on core samples from Paleogene reservoirs of the UK Central North Sea revealed distinct signatures around the oil water interface. Rapid increases in susceptibilities at temperatures < 250 °C were observed for samples around the oil water interface unlike the main oil leg where alteration involving increase in susceptibility occurred at significantly slower rates and higher temperatures. The HT-χ data together with Mössbauer measurements revealed that the variation in alteration characteristics is due to the increasing concentration of hexagonal pyrrhotite and/or lepidocrocite around the oil water interface. Hexagonal pyrrhotite was identified in reservoirs existing at temperatures of < 80 °C, while lepidocrocite dominated the signature around the contact of deeper reservoirs. These observations suggest that the precipitation of hexagonal pyrrhotite is related to OWTZ centred biogenic activities i.e., biodegradation. The dominance of lepidocrocite in deeper diagenetic settings has been related to hydrolysis of hydrocarbon at the oil water interface, together with cessation of biogenic activities.